PENGELOLAAN PEMUNGUTAN RETRIBUSI PEMERIKSAAN ALAT PEMADAM KEBAKARAN OLEH BADAN PENANGGULANGAN BENCANA DAN PEMADAM KEBAKARAN KOTA PEKANBARU TAHUN 2011-2015 - Ramadhani, M. Ryan; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The study focuses on how the management of the levy charged for inspection of fire extinguishers by the Agency Penanggulangangan disaster and Pekanbaru City Fire the years 2011-2015 in which the proceeds of the levy inspection of fire extinguishers years 2011-2015 never increase and good progress in retribution whereas annually an increase that segnifikat to levy service user checks fire extinguishers it is characterized by the many fire extinguishers are increasing every year. This study aims to determine how the process of managing the levy charged for inspection of fire extinguishers that are managed by the Agency for Disaster Management and Fire Pekanbaru the years 2011-2015 and also to determine any factors that hinder the process of managing levy inspection of fire extinguishers that exist in the city pekanbaru so constrained in the achievement of the target realization of retribution.Keywords: Management, Retribution, Fire extinguisher